Role performance of Village Panchayat in the field of Agricultural Development and Village welfare in Unnao District of Uttar Pradesh - Dube, Ritesh; Yadav, O. P.; Kumar, Sheelesh; Singh, Amit Kumar (Indian Journal of Extension Education, 2016)
The project intended to study the role performance of Village Panchayants with respect to role in the field of Agricultural  Production and Social welfare of village community the histogram of specific role performed by the Village Panchayats  showed the frequency of responses perceived by the respondents.It was analysed that the maximum (93.75%) respondents  opined in favour of motivation farmers for availing financial and technical help by the local cooperatives (87.50%) by  making efforts for the availability of chemical fertilizers, pesticides etc. (83.75%) of technology transfer for the  maintenance of livestock and making efforts for improving cattel breeds (78.75%) of assisting for assured supply of  irrigation by canal and public tube-well (75.00%) or preparation of agricultural production plan (75.00%) by arrangement  for reviving the traditional village cottage industries (68.75%) by making efforts for undertaking user reclamation  (62.50%) of distribution of land among landlesses, (62.50%) of organising fair and meals and (56.25%) to organise and  layout field demonstration. It was also analysed the social services and maintenance of buildings, provision of drinking  water facilities. It was calculated that respondents opined in favour of the perception that the agricultural sub-committee  was responsible for pooling and making available agricultural resources to the cultivators. It was studied the social  welfare committee was worked for constructing Village Panchayats buildings, culverts, irrigation channels, wells and  tanks, improvement of family welfare programme, contagious diseases and epidemic and eradication of social evils like  gambling, untouchability etc.
Keywords: Cottage industries; epidemic; histogram; untouchability; village panchayats